(3JdNjU GdeaJGMs - (3GdcGTj Ch GdcGTGfj, ZjGK GdOjf, nLreTpjO Hf eSYhO Hf eMehO Hf eMeO, (B832 (3g`s ((3jMji Hf SdWGf Hf eMeO GdMSjfj WHWHGFjs)
(3ChdgG (B:s
(3GdMeO ddg (B... (3deG aQZJ Yf JMQjQ cJGHj GdeSei HeaJGM GdMSGH aGfJNHJ efg gPG GdeNJUQ ajeG dGHO Yfg ddeHJOFjf hSejJg (B.. (3hLYdJg eTJedG Ydi KdGKjf aUdG eSJYjfG HGddg hMOg GdYRjR ; GdaUd GdChd (B...s
(3BNQgG (B:s
... (3GdSGHYI EPG VQH YOO aj YOO ajchf LPQ GdMGUd eSGhjG dMGUd VQH LPQ CMO GdYOOjf aj LPQ GdBNQ hdfNJe GdcdGe gGgfG MGeOjf ddg JYGdis
(3JHUQI GdYfhGf (B:s
(3eaJGM GdMSGH ddeDdas
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B2\136s
(3cTa GdXfhf (B1\1760s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdQjGVjGJs